Efficacy and safety associated with the use of the Surfacer® Inside-Out® Access Catheter System: Results from a prospective, multicenter Food and Drug Administration–approved Investigational Device Exemption study. Issue 1 (January 2021) - Razavi, Mahmood K; Peden, Eric K; Sorial, Ehab; Ross, John R; Aruny, John E; Pflederer, Timothy A; Wasse, Haimanot; Haskal, Ziv J
Purpose: Thoracic central venous obstruction is commonly associated with the use of central venous catheters. The Surfacer System to Facilitate Access in Venous Occlusions Study was an Food and Drug Administration–approved US Investigational Device Exemption study designed to evaluate the performance and safety of the Surfacer System when used to facilitate central venous access in patients with thoracic central venous obstruction. Methods: Thirty patients were enrolled in this prospective, multicenter, single-arm study between December 2017 and May 2019. Device performance and adverse events were collected peri-procedurally and at discharge. Enrollment included 15 female and 15 male subjects with a mean age of 55.5 ± 12.9 (range: 30–79) years. Twenty-eight patients (93.3%) required central venous access for hemodialysis access. Locations of thoracic central venous obstruction were graded from 1 to 4 based on severity and extension of venous occlusions. Seven patients (23.3%) had type 1, 6 (20.0%) type 2, 16 (53.3%) type 3, and 1 (3.3%) type 4 obstruction. Results: Successful central venous catheter placement was achieved in 27 of 30 patients (90.0%). The procedure was discontinued in three (10.0%) due to tortuous anatomy discovered intraprocedurally. All 27 patients with successful CVC placement achieved adequate catheter patency and tip positioning with a mean overall procedural time and time to achieve central venous access with the Surfacer System being 44.1 ± 30.6 and 19.1 ± 25.1 min, respectively. There were no device-related adverse events or catheter malposition. Conclusion: The results of the SAVEUS Study confirm the safety and efficacy of the Surfacer System and the Inside-Out procedure when used for the placement of right-sided central venous access in patients with thoracic central venous obstruction.